Development of field deployable fiber bragg grating interrogator / Abdul Halim Poh Yuen Wu - Abdul Halim, Poh Yuen Wu (2013)
This study aims to address the main problems of analyzing fiber Bragg grating (FBG) sensors in field, which consists of two main issues. First is the usage of optical spectrum analyzers (OSAs) and broadband light sources. Both are bulky instruments, and especially the OSA being heavy and costly (ranges between RM100-200k for the OSA and RM20k for the light source). These equipments exhibit a very large wavelength range (1.1 μm for the OSA, 35nm for the light source), which is unnecessary for the otherwise much less feature-demanding FBG. Second, the applications considered for the development of this optical sensor interrogation prototype is for applications which demands data to be logged from every few hours to days. Therefore, a study is conducted to design and construct a fully portable, low-cost and low-powered interrogator which is specifically designed to read FBGs within the C-band (1530-1565nm). This resulted in the construction of an Erbiumdoped fiber amplifier (EDFA) ring laser, but the actual strength of this work lies within the integration with the electronic circuitry, which makes it portable and readily deployable. This work resulted in four milestones. The first is the successful construction of an optimized EDFA ring laser, the robust and low-power driving circuitry design and construction of the 980nm laser pump, the actuation and digitization of a tunable bandpass Filter (TBF) to render the laser’s tunability tangible in the electronics realm, and finally the success in interrogating an FBG itself, which finalizes the work. A spectral profile similar to the one obtained via an OSA can be reverse-mapped using this interrogation scheme. The central wavelength of the reflected signal can be obtained via this method with minimum error of ±0.09nm.